2021
DOI: 10.3390/en14061561
|View full text |Cite
|
Sign up to set email alerts
|

Time-Multiplexed Self-Powered Wireless Current Sensor for Power Transmission Lines

Abstract: Current measurement is a key part of the monitoring system for power transmission lines. Compared with the conventional current sensor, the distributed, self-powered and contactless current sensor has great advantages of safety and reliability. By integrating the current sensing function and the energy harvesting function of current transformer (CT), a time-multiplexed self-powered wireless sensor that can measure the power transmission line current is presented in this paper. Two operating modes of CT, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A generalization of the spectral characteristics of the signals induced by the electromagnetic radiation of the nearby impulse streamer corona flash on model elements of different types showed the close values of all frequency parameters inside every group of the electric amplification coefficient for rod and elongated model elements (Tables 6 and 7). The maximal values of the upper level of the characteristic frequency in the wavelet spectrum of the induced signal (the electromagnetic radiation of upward streamers was sometimes in the range of 1.0-1.5 GHz) were discovered in group II (an amplification coefficient of [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Group III (amplification coefficient > 25) showed similar, but slightly lower, values.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A generalization of the spectral characteristics of the signals induced by the electromagnetic radiation of the nearby impulse streamer corona flash on model elements of different types showed the close values of all frequency parameters inside every group of the electric amplification coefficient for rod and elongated model elements (Tables 6 and 7). The maximal values of the upper level of the characteristic frequency in the wavelet spectrum of the induced signal (the electromagnetic radiation of upward streamers was sometimes in the range of 1.0-1.5 GHz) were discovered in group II (an amplification coefficient of [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Group III (amplification coefficient > 25) showed similar, but slightly lower, values.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 99%
“…These systems use collected data to form control signals that make operational decisions [1][2][3][4][5][6][7]. At the same time, functional problems continue to appear during the use of digital technology and computing systems in the online monitoring of the air transmission lines (e.g., sensors of various kinds, analog-digital converters for the processing of recorded signals, and antenna and receiver-transmitting devices of different shapes and sizes [6][7][8][9][10]) under the influence of thunderclouds and lightning. Most often, these devices are rods, cylindrical, or flat.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain stable grid operations, it is crucial to monitor the conditions of transmission lines, such as the current, 1 ice-covering, 2 and galloping. 3 Line conditions can be easily monitored using wireless monitoring sensors that are extensively installed on transmission lines.…”
Section: Introductionmentioning
confidence: 99%
“…Remote monitoring systems are increasingly being introduced into the management of transmission lines and become an important element of digital power industry [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During their exploitation, it was observed that the functionality of the artificial intelligence elements used in such systems (i.e., all devices that contain electromagnetic parts, e.g., sensors; analog-digital converters for processing of recorded signals; antennas, etc.) may be compromised under the influence of lightning and atmospheric electricity [3,11,12]. It is not entirely clear how the discharge phenomena forming on both rod and elongated ground objects under the influence of thunderclouds and lightning (e.g., flashes of streamer corona, ascending leaders, the main discharge) and the electromagnetic radiation they create will affect functioning of such elements [13,14].…”
Section: Introductionmentioning
confidence: 99%